2011
DOI: 10.1172/jci60417
|View full text |Cite
|
Sign up to set email alerts
|

EGFR as a therapeutic target for human, canine, and mouse ACTH-secreting pituitary adenomas

Abstract: Cushing disease is a condition in which the pituitary gland releases excessive adrenocorticotropic hormone (ACTH) as a result of an adenoma arising from the ACTH-secreting cells in the anterior pituitary. ACTH-secreting pituitary adenomas lead to hypercortisolemia and cause significant morbidity and mortality. Pituitarydirected medications are mostly ineffective, and new treatment options are needed. As these tumors express EGFR, we tested whether EGFR might provide a therapeutic target for Cushing disease. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
173
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(179 citation statements)
references
References 59 publications
4
173
1
1
Order By: Relevance
“…EGF treatment increased Pomc transcription and ACTH secretion in EGFR-overexpressing corticotrophinoma cells and in corticotroph tumors from dogs and human patients with CD (51). EGFR overexpression in the mouse corticotrophinoma AtT-20 cells (that do not express the receptor) triggered basal Pomc transcription (28).…”
Section: Egfr and Corticotroph Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…EGF treatment increased Pomc transcription and ACTH secretion in EGFR-overexpressing corticotrophinoma cells and in corticotroph tumors from dogs and human patients with CD (51). EGFR overexpression in the mouse corticotrophinoma AtT-20 cells (that do not express the receptor) triggered basal Pomc transcription (28).…”
Section: Egfr and Corticotroph Functionmentioning
confidence: 99%
“…EGFR overexpression in the mouse corticotrophinoma AtT-20 cells (that do not express the receptor) triggered basal Pomc transcription (28). All these effects were mediated through Erk1/2 and acted on the proximal to initiation site of the Pomc promoter (28,51). Treatment with the EGFR tyrosine kinase inhibitor gefitinib decreased ACTH synthesis and secretion in human corticotrophinomas in vitro and decreased tumor growth and corticosterone levels in a xenograft corticotroph tumor animal model, where it ameliorated the symptoms of CD (51).…”
Section: Egfr and Corticotroph Functionmentioning
confidence: 99%
“…The positive expression of dopamine receptor D2 (DRD2), somatostatin receptors (SSTRs), and EGFR have been shown to predict drug susceptibility to dopamine agonists, somatostatin analogs, and TK inhibitors respectively (12,13,17). In contrast, the negative expression of O 6 -methylguanine DNA methyltransferase (MGMT) and the DNA mismatch repair protein MSH6 have been associated with tumor responsiveness (18,19) and resistance to temozolomide (20) respectively.…”
Section: Introductionmentioning
confidence: 99%
“…POMC promoter activity by EGF required a -323 to -200 bp element that includes Tpit/Pitx sites [18]. Recently Reincke et al reported that ubiquitin-specific peptidase 8 (USP8) gene mutations were found in a high percentage of corticotroph adenomas [19,20].…”
Section: Discussionmentioning
confidence: 99%